Permeability characteristics of human endothelial monolayers seeded on different extracellular matrix proteins - Arjan Nooteboom; Thijs Hendriks; Irene Ottehöller; Cees. J. Van Der Linden (Mediators of Inflammation)
Objective: To investigate whether endothelial monolayer permeability changes induced by inflammatory mediators are affected by the extracellular matrix protein used for cell seeding.